Optimising blood glucose control with portioned meal box in type 2 diabetes mellitus patients: a randomised control trial - Maneesing, Tanu-udom; Dawangpa, Atchara; Chaivanit, Pechngam; Songsakul, Sudjai; Prasertsri, Piyapong; Yumi Noronha, Natália; Watanabe, Lígia Moriguchi; Nonino, Carla Barbosa; Pratumvinit, Busadee; Sae-Lee, Chanachai (Frontiers in Nutrition, 2023)
Background: The impact of dietary factors on glycaemic control in type 2 diabetes mellitus (T2DM) is well established. However, the effectiveness of transforming portion control into a practical innovation for glycaemic control in T2DM has not yet been established for counselling in nutrition. The aim of this study was to compare the effect of general counselling in nutrition (GCN) and a portioned meal box (PMB) on fasting blood glucose, glycated haemoglobin (HbA1c) and body composition.Methods: A randomised, parallel intervention trial was conducted over 12 weeks, with GCN: carbohydrate portion control concept by using food exchange lists (n=25) and PMB: portioned meal box was set by energy requirements (n=25).Results: Both GCN and PMB demonstrated reductions in HbA1c levels at the 6 th and 12 th weeks compared to baseline. However, no significant difference in HbA1c was observed between GCN and PMB at either the 6 th or 12 th week. Using PMB at least four times a week significantly decreased HbA1c during the intervention period (p=0.021 and p<0.001 for weeks 6 and 12 when compared with baseline, respectively). Changes in body composition were observed: body weight decrease in PMB only, body fat decrease and constant muscle mass in both groups. Both methods tended to relieve hunger and increased satiety in both groups. The satisfaction evaluation showed that participants preferred to use PMB over GCN (p=0.001). Additionally, participants consumed less energy, carbohydrate and fat in PMB (p=0.001, p=0.019 and p=0.001, respectively) and less energy and fat in GCN (p=0.006 and p=0.001, respectively). Conclusion: A better diet, either through GCN or PMB, can play an important role in improving dietary intake compliance and controlling blood glucose.